Tribological response of laser-textured Ti6Al4V alloy under dry conditions and lubricated with Hank's solution. (August 2021) - Conradi, M.; Kocijan, A.; Klobčar, D.; Podgornik, B.
Abstract: A nanosecond laser was used to define different morphologies of a Ti6Al4V surface: lines, crosshatching and dimples. We analysed the influence of the surface morphology, texture density and orientation (parallel, perpendicular and at 45°) on the friction/wear under dry and lubricated (Hank's solution) sliding conditions to evaluate the specific laser texturing of Ti alloys for biomedical applications. Under dry conditions, the lowest steady-state coefficient of friction was measured for dimples, whereas in Hank's solution the lines and crosshatching showed better frictional characteristics after running-in and the removal of the bulges around the laser textures. In terms of wear resistance, the low-density lines pattern and particularly the dimples were the most promising in contact situations likely to occur during starved/dry-lubrication conditions. Highlights: Laser-texturing of Ti6Al4V surface: lines, crosshatch and dimple texture. Friction/wear study under dry/lubricated conditions:effect of texturing direction. Reduced friction in Hank's solution for lines and crosshatch texture. Combination of abrasive and adhesive wear under both sliding conditions. Biomedical applications:transition form lubricated to starved/dry conditions.